Pengaruh Strategi Role Playing Terhadap Keterampilan Komunikasi Siswa Pada Mata Pelajaran PKn di Kelas III MIN 4 Medan - Azzahra, Nabila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to find out how far the influence of role playing strategies on students' communication skills in Class III MIN 4 Medan for the 2023/20024 Academic Year. The type of research used is Pre-Experiment with the type of One Group Pretest – Postest Design. The population in this study is all students of class III MIN 4 Medan. The sample of this study was 28 students from classes III-B who were selected through the Purposive Sampling technique. The data analysis used in this study is the normality test, linearity test, simple linear regression test, Determination Coefficient test (R square) test and hypothesis test. Based on the results of the study, the average score of the pretest communication skills test was 55.35 and the posttest was 79.07. The results of the t-test with regression analysis and at the level of significance ? = 0.05 were obtained t calculated > t table which was 10.480 > 1.706 and and a sig. (0.000) < 0.05, then Ho is rejected. So it was concluded that there was a significant influence of role playing strategies on students' communication skills in PKn subjects in Class III MIN 4 Medan.